Upgrading home molded case circuit breaker for automatic turn on after tripping - Syed Hassan, Syed Mohd Afdhal (2010)
This report describes the upgrading home main circuit breaker, Moulded Case Circuit Breaker (MCCB) from manual switch ON to automatic switch ON after tripping. This report covered all aspect of design and development. The types and circuit breaker operations that already been used as electrical circuit protection have been discussed. The suitable mechanism called plunger, which will help to pull up circuit breaker to tum ON position. Peripheral Interface Controller (PIC) has been used as the plunger main circuit controller that will operate at five times. The numbers of operation will indicate with five LED. Plunger mechanism has been employed to reset the circuit breaker to its ON position to meet the objective of the project.